DESIGN A RENEWABLE ENERGY MODEL BASED-ON MODIFICATION OF IMPEDANCE NETWORK (REM-MIN) - Ali Mohammed Elaibi (Journal Park Publishing, 2024)
The most energy used nowadays are based on those design and models for producing high energy but with minimizing its effects on the environments. To do so, Renewable Energy Model Based-on Modification of Impedance Network (REM-MIN) is proposed. The mentioned modification could be seen on impedance network, and such network has built based on proposed network flow scheme. In this article, voltage performance analysis is performed based on new criteria called free boost control which has been utilized in almost renewable energy applications. This article also making an analysis of the impact of conventional inverters to overcome the drawback of nowadays source inverters such as VSI, CSI and ZSI by proposing a quasi-Z source inverter (QZSI). The QZSI produce almost inverters operations namely hybrid inverter such as from DC to DC and from AC to AC, and also their hybrid such as from DC to AC and vice versa. Also, it may be used for each buck and boost operation, using the shoot through state. The achieved goals for this paper are producing both main properties which are stability and reliability. The modelling of the proposed model has been built based on MATLAB/Simulink environment.
Keywords: Renewable energy, impedance network, quasi-Z source inverter, stability, reliability.